Morphometric and morphological variation in Myotis simus Thomas (Chiroptera, Vespertilionidae), with an appraisal of the identity of Myotis guaycuru Proença based on the analysis of the type material - Moratelli, Ricardo; Peracchi, Adriano L.; de Oliveira, João A. (Zootaxa, 2011)
Twelve species are recognized in the South American bat genus Myotis Kaup (Vespertilionidae, Myotinae), with several nominal forms currently regarded as synonyms, among them Myotis guaycuru Proença, 1943. Its holotype, so far the only specimen assigned to the species, has not been examined in recent taxonomic reviews. To address the taxonomic status of M. guaycuru, we located and redescribed its holotype and compared it to representatives and/or descriptions of all South American species in the genus. Qualitative traits, namely the plagiopatagium attached at ankles, the short and wooly fur and the lingually displaced P3, unambiguously assign the holotype of M. guaycuru to Myotis simus Thomas (1901). The analysis of cranial variation and pelage color across a wide geographical range of M. simus reveals morphometric and morphological discontinuity between Bolivian and Amazonian/Peruvian samples, the latter including topotypes of M. simus. The holotype of M. guaycuru was found to be morphometrically and morphologically more similar to these Amazonian samples than to the geographically nearer Bolivian sample, preventing the use of this nominal form to refer to the Bolivian population if its distinction suggested by morphometric analyses is confirmed by the analyses of other character systems.